The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/10410236.2014.888629
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Evidence Type and Narrative Type on HPV Risk Perception and Intention to Obtain the HPV Vaccine

Abstract: This research examines the influence of evidence type (statistical, narrative, or hybrid) and narrative type (first-person or third-person) on risk perception about human papillomavirus (HPV) and behavioral intention to get the HPV vaccine. In total, 174 college students who had not received the HPV vaccine participated in a controlled experiment. Results show that the hybrid message containing both statistical and narrative descriptions of HPV resulted in greater perceived risk of getting HPV than either of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 33 publications
4
100
3
4
Order By: Relevance
“…This research contradicts past research, which found that first-person narratives lead to elevated risk perceptions, as well as increased attitude change, as compared to third-person narratives (De Gaaf et al, 2012;Nan et al, 2015). It is especially surprising that this work did not find differences in risk perceptions, as this work used nearly identical items to measure perceived risk as those used by Nan et al (2015).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This research contradicts past research, which found that first-person narratives lead to elevated risk perceptions, as well as increased attitude change, as compared to third-person narratives (De Gaaf et al, 2012;Nan et al, 2015). It is especially surprising that this work did not find differences in risk perceptions, as this work used nearly identical items to measure perceived risk as those used by Nan et al (2015).…”
Section: Discussioncontrasting
confidence: 75%
“…, as well as leading to higher risk perception in a health context (Nan et al, 2015), when compared to third-person narratives. These findings, demonstrating that first-person narratives may be more persuasive than third-person narratives, led to testing the following hypotheses in the new context of tanning among female college undergraduates: H1: Participants who receive a first-person message will report higher levels of risk perception regarding tanning beds, as compared to those who receive a thirdperson message.…”
mentioning
confidence: 99%
“…For example, only slightly more than one-half of our population knew that three out of four people will have HPV at some point (53%). Understanding the high prevalence of HPV may influence perception of risk and therefore motivate vaccination (Nan, Dahlstrom, Richards, & Rangarajan, 2015). Participants were somewhat unaware of the consequences of HPV for men (44% correctly knew that HPV can cause serious health problems for men) and opportunities for vaccination for men (40% incorrectly thought the HPV vaccine is only for females).…”
Section: Resultsmentioning
confidence: 97%
“…Narratives may offer a way to overcome these barriers, by engaging readers on both a cognitive and affective level [Green and Brock, 2000;Hinyard and Kreuter, 2007]. Empirical research in this field remains scarce and the effects of narratives on health-related decision appear inconsistent [Winterbottom et al, 2008], but these discrepancies may be partially accounted by the variability in the format and the structure of narratives [Dahlstrom, 2015;Nan et al, 2015].…”
Section: Narratives and Charactersmentioning
confidence: 99%